Tort Theories and Tort Statutes - Goudkamp, J; Murphy, J (Sweet and Maxwell, 2014)
Although the legislature has made significant inroads into tort law, tort theorists have focused their attention overwhelmingly on the common law. Serious consideration has never been given to the challenges that statutory tort law poses for theories of tort law. In this article we begin to redress this omission by examining the implications of statutes for corrective justice and rights-based theories of tort law. Our central task is to determine whether these leading theories accurately explain tort law once statutory tort law is taken into account. As a precursor to this analysis, we consider whether statutes form part of tort law (some influential theorists believe or arguably believe that they do not). We contend that statutes are part of tort law and that the theories under examination fail to explain important aspects of statutory tort law. Partly because of this failure, they are not satisfactory accounts of the whole of tort law, which is often how they are presented by their proponents.